Stratosphereâ€“Troposphere Coupling during Sudden Stratospheric Warmings with Different North Atlantic Jet Response - Verónica Martínez-Andradas; de la CÃ¡mara, Alvaro; Zurita-Gotor, Pablo (Journal of Climate, 2023)
Sudden stratospheric warmings (SSWs) are extreme disruptions of the wintertime polar vortex that can alter the tropospheric weather for over 2 months. However, the reasons why only some SSWs have a tropospheric impact are not yet clear. This study analyses the tropospheric impact of SSWs over the Atlantic region as measured by the latitudinal displacement of the North Atlantic eddy-driven jet following SSWs. We use reanalysis data for the period 1950–2020 to examine differences in the stratospheric and tropospheric circulation for SSWs with an equatorward (EQ) or a poleward (POLE) shift. Our results show a stronger and more persistent Northern Annular Mode (NAM) signal in the lower stratosphere for EQ than for POLE, beginning 2 weeks before the onset date. In the troposphere, we find precursory signals of the Atlantic jet behavior over Siberia, consistent with previous studies, and also over the central North Pacific and central Europe. In particular, our results suggest that the noncanonical poleward jet shift response to SSWs is in part modulated by circulation anomalies over the central North Pacific, and that these are in turn connected to the cold phase of El Niño–Southern Oscillation. Further analysis of the enhanced predictability given by these precursors suggests that the sign of the lower-stratospheric NAM and the geopotential anomalies over the central North Pacific significantly affect the probability of having an EQ or POLE response of the Atlantic jet. Peer reviewed